Characteristics of desirable ambulatory health and oral healthcare from the perspective of community-dwelling people aged 80 and over—a qualitative examination. (20th November 2022) - Herrler, Angélique; Kukla, Helena; Barbe, Anna Greta; Vennedey, Vera; Stock, Stephanie
Abstract: Background: people aged 80 and over frequently have diverse and complex health trajectories, which has been well studied. But their oral health is seldom included in care models. To realise comprehensive healthcare, both general and oral ambulatory (i.e. outpatient) healthcare need to be explored and conceptualised equally. Objective: to elicit what matters to very old people regarding ambulatory health and oral healthcare. Methods: interviews were conducted with non-institutionalised people aged 80 and over living in the area of Cologne, Germany. They were interviewed regarding their experiences of and views on ambulatory healthcare and oral healthcare care, respectively. Thematic analysis was performed to understand their motives and elicit relevant characteristics of desirable health services. Results: from the interviews with 22 participants, 16 characteristics of good healthcare were described. These were generally similar for both general and oral healthcare and had a particular focus on patient–provider interaction and the organisation of care. However, regarding oral healthcare, the participants focused more strongly on the technical–medical skills of professionals and the perceptible treatment results and were more concerned about costs. It was noticeable that older people had the urge to differentiate themselves from 'others unnecessarily using health services'. They were unaware of possible future oral health deterioration and the resulting future needs. Conclusions: characteristics of good health and oral healthcare from the perspective of older people should be incorporated to ensure patient-centredness in care models. Older patients, as well as healthcare providers, need to be sensitised to their oral health needs to realise comprehensive healthcare.